2023
DOI: 10.1136/bmjsem-2023-001553
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure, dietary intake and energy availability in female professional football players

Abstract: ObjectivesTo quantify energy expenditure and intake in professional female footballers playing on a national and/or international level. Second, to determine the prevalence of low energy availability among these players, defined as <30 kcal/kg fat-free mass (FFM)/day.MethodsFifty-one players completed a 14-day prospective observational study during the 2021/2022 football season. Energy expenditure was determined using the doubly labelled water method. Energy intake was assessed using dietary recalls, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
5
16
0
Order By: Relevance
“…While overuse injuries are the most common types of injuries among athletes in endurance and other non-contact sports, overuse and acute injuries occur frequently in contact sports 36. High injury score must therefore be interpreted with caution and in relation to injury type and underlying causes 35 36. In the present study, athletes’ answers to open-ended questions about injury types sustained in the past year were not sufficiently detailed to elaborate further on.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…While overuse injuries are the most common types of injuries among athletes in endurance and other non-contact sports, overuse and acute injuries occur frequently in contact sports 36. High injury score must therefore be interpreted with caution and in relation to injury type and underlying causes 35 36. In the present study, athletes’ answers to open-ended questions about injury types sustained in the past year were not sufficiently detailed to elaborate further on.…”
Section: Discussionmentioning
confidence: 89%
“…While LEAF-Q total, gastrointestinal and menstrual scores were associated with many of the LEAM-Q-derived scores, no associations were found between any of the LEAM-Q derived scores and the LEAF-Q injury score. Accordingly, recent studies have reported that the LEAF-Q injury score lacks specificity when administered in sports other than endurance and aesthetic 35 36. The injury score is only based on questions regarding number and duration of absences from training or competition in the past year due to unspecified injuries 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case for the research base that supports the provision of an evidence-based sports nutrition programme, where the energetic requirements of elite female soccer players are now only beginning to be understood. Indeed, we [5] and others [6] have recently reported the direct assessment of adult players' energy expenditure (EE), assessed using the gold-standard, doubly labelled water technique. Such reports document absolute energy expenditures of 2693 ± 432 and 2918 ± 322 kcal•day −1 in a cohort of English (international competition) and Norwegian (domestic competition) players, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Such reports document absolute energy expenditures of 2693 ± 432 and 2918 ± 322 kcal•day −1 in a cohort of English (international competition) and Norwegian (domestic competition) players, respectively. Notwithstanding the potential for dietary under-reporting, it is noteworthy that both studies also highlighted that the players' selfreported energy intake (EI) was below the recommended values, such that low energy availability (LEA, as classified according to the published values of <30 kcal•kg FFM −1 •day −1 ) was estimated to occur in 23 [5] and 88% [6] of the players on training days. Such data also agree with the prevalence of LEA that was reported in English players playing in their respective domestic league [7].…”
Section: Introductionmentioning
confidence: 99%